The Development of Education in Afghanistan (Journal of Educational Sciences, 2017)
This article deals with the development of education in Afghanistan, including the history of the development of higher education. The article presents the origins of the education system formation, starting from the beginning of the XX century to the modern stage, and the higher education system - from the second half of the XX century, as the main reasons for slow progress of development of education indicates a period of struggle of the Afghan people to foreign aggression. The article describes the development of education periods: during the reign of Khan Nabibulah, Amanulah Khan, Zaher Khan, Communists,  Mujahedeen, the Taliban, Karzai Ahmadi. The study focuses on the history of secular and religious schools, and also the existence of different standards of education that have been upgraded in accordance with the traditional values of the country. As one of the main reasons for the low level of development of the education system in Afghanistan, indicated the need for and dependence on external sources of financing, the relentless struggle for independence for centuries, as well as the devastating effects of the reign of the Taliban. The authors point to the poor quality of the implementation of standards of education, poor infrastructure, lack of teacher trainin
Keywords: education; school; religious school; the educational system; Taliban; government